PENERAPAN MODEL PEMBELAJARAN PARTICIPATION BASIC INTRUCTIONAL (PBI) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA DALAM PEROSES PELAJARAN MATEMATIKA DI KELAS X MA NW MAFAZA - Hayaturraiyan, Hayaturraiyan (LP2M STAI Darul Kamal NW Kembang Kerang, 2023)
This research aims to describe efforts to increase student learning activeness in the Mathematics learning process in class X MA NW Mafaza. This type of research uses action research, the subject of this research is MA NW Mafaza class X as many as 18 students. The research object is active learning using the participation basic instructional learning model. Data collection techniques using observation sheets, interview sheets and questionnaires. Data analysis techniques using qualitative analysis techniques and quantitative analysis techniques. Through this action research, it can be found that there is an increase in student activity in the mathematics learning process regarding three-variable linear equation systems. This is proven from the results of observations of student learning activity before being given action, which was in the very low category, namely only 33%, after being given action in cycle I, student activity increased to the medium category, namely 61% of data from observation results and 66% of data from questionnaires. In cycle II, student learning activity rose again to a high category, namely 72% of data from observations and 77% of data from questionnaires. Based on the results of this study, it can be a reference for teachers to improve student learning outcomes.